Edukasi Program PENA (Peduli Nyeri Anda) sebagai Upaya Promosi Kesehatan di Padukuhan Ngemplak Kembangarum - Yulianto Yulianto; Adilla Pratama Putri; Akhmad Dzaikra Ramahani; Ardelia Putri Mahendra; Hana Atika Azah Eskanda; Hesti Anjani Putri; Nanda Ghefira Az Zahra; Raissa Laila Rahma; Restika Mithari; Shelvi Anggraini; Shopia Nur Fauziah; Viviane Annisa (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
Pain is a common health problem that can reduce productivity and quality of life. The high rate of self-medication in pain management and the wide variety of over-the-counter medications often lead to the misuse of drugs. The PENA (Peduli Nyeri Anda) program is a health promotion activity that aims to increase the community's knowledge in Padukuhan Ngemplak Kembangarum about safe and rational pain management. This study used a quasi-experimental, one-group pretest-posttest design through health education activities. The results indicate that PENA education significantly increased community knowledge regarding pain management (p < 0.001), with income identified as the most correlated factor. This program is effective as a promotive effort, although further research with a larger sample size and more specific variables is required to strengthen the generalization of the findings.